2006
DOI: 10.1590/s0101-20612006000400021
|View full text |Cite
|
Sign up to set email alerts
|

Produção de geléia de jambolão (Syzygium cumini Lamarck): processamento, parâmetros físico - químicos e avaliação sensorial

Abstract: A fruta jambolão (Syzygium cumini Lamarck) é uma fruta de coloração roxa intensa e sabor agradável. Dado que não há na literatura nenhum relato de seu aproveitamento industrial, a produção de geléia de jambolão tornou-se uma interessante atividade de pesquisa. Este trabalho objetivou a elaboração e a avaliação das características físico-químicas e sensoriais da geléia obtida do jambolão. A fruta apresentou a seguinte composição química: cinzas, 0,34%; lipídeos, 0,30%; proteínas, 0,67%; carboidratos, 10,07%; fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
25
2
22

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 18 publications
8
25
2
22
Order By: Relevance
“…Lago-Vanzela et al (2011) found satisfactory acceptance of peel and pulp caja-manga jams, with mean scores of 7.19 and 6.49, respectively, between the hedonic terms of "like slightly" and "like very much". A similar result was observed by Lago et al (2006) working with jambolan jam, who found an average score of acceptance for flavour equal to 7.…”
Section: Resultssupporting
confidence: 84%
“…Lago-Vanzela et al (2011) found satisfactory acceptance of peel and pulp caja-manga jams, with mean scores of 7.19 and 6.49, respectively, between the hedonic terms of "like slightly" and "like very much". A similar result was observed by Lago et al (2006) working with jambolan jam, who found an average score of acceptance for flavour equal to 7.…”
Section: Resultssupporting
confidence: 84%
“…A acidez total não deve exceder a 0,8%, e o mínimo indicado é de 0,3%. Quanto ao pH, sugere-se um pH máximo de 3,4, sendo que abaixo de 3,0 ocorre uma tendência à sinérese (Lago, Gomes & Silva, 2006). A geleia do suco da casca de abacaxi apresentou-se em conformidade com estes valores.…”
Section: Resultsunclassified
“…however, national fruit production has a great expansion potential once several native and exotic fruits are not economically explored. Attempts to turn such unexplored cultures into reasonable ones are in course, mainly for atemóia, maná, canistel, mirtilo, lichia, physalis and star fruit (LAgo;gomES;SILVA, 2006). P. peruviana is an exotic fruit that belongs to the Solanaceae family and Physalis genus from Amazon and Andes.…”
mentioning
confidence: 99%